2003
DOI: 10.1002/art.11140
|View full text |Cite
|
Sign up to set email alerts
|

Complete remission of experimental arthritis by joint targeting of glucocorticoids with long‐circulating liposomes

Abstract: Objective. To increase the therapeutic activity of glucocorticoids in experimental arthritis by encapsulation in long-circulating polyethylene glycol liposomes, which have shown the ability to preferentially accumulate in inflamed joints after intravenous administration.Methods. Rats with adjuvant-induced arthritis (AIA) were treated intravenously with liposomal and free prednisolone phosphate (PLP) a few days after the first signs of disease. The effect on paw inflammation scores during the weeks after treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
239
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 281 publications
(256 citation statements)
references
References 22 publications
12
239
0
5
Order By: Relevance
“…Levels of localization of all 3 types of liposomes in the inflamed skin were higher than those in normal skin. Control liposomes (RAD-PEG-L or PEG-L) most likely localized in the inflamed skin due to the enhanced permeability and retention effect, as demonstrated for longcirculating liposomes at sites of inflammation or infection (25,48). It has been reported that enhanced permeability and retention-mediated extravasation increases with increasing circulation time of the liposomes (31).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Levels of localization of all 3 types of liposomes in the inflamed skin were higher than those in normal skin. Control liposomes (RAD-PEG-L or PEG-L) most likely localized in the inflamed skin due to the enhanced permeability and retention effect, as demonstrated for longcirculating liposomes at sites of inflammation or infection (25,48). It has been reported that enhanced permeability and retention-mediated extravasation increases with increasing circulation time of the liposomes (31).…”
Section: Discussionmentioning
confidence: 98%
“…However, in previous studies the effects of free corticosteroids such as DEXP and prednisolone phosphate in relation to the efficacy of liposomal formulations have been carefully assessed in this arthritis model as well as in a murine collageninduced arthritis model. In all of these studies a single administration of free drug exerted minor or no efficacy in alleviating the inflammation, whereas liposomal formulations were efficacious (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of MTXliposomes was reduced when PEG-liposomes were used, probably due to reduced uptake by macrophages within the synovium (24). More recently, Metselaar and colleagues demonstrated that liposomal prednisolone phosphate was significantly more efficacious than the same dose of the free drug in 2 murine arthritis models (25,26). They were able to show that the intravenously administered PEG-liposomes homed to the inflamed joints and that there was an associated reduction in cartilage damage.…”
Section: Liposome Formulationsmentioning
confidence: 99%
“…This is the first time that specific targeting of liposomes has been shown to be effective in arthritis and represents an important step forward as well as raising some intriguing questions. Although free corticosteroid was not used as a control in these experiments, previous work has shown dramatic differences in efficacy of nontargeted liposomal steroid over the free drug, along with dramatic reductions in cartilage damage (25,26). There remains a significant minority of patients with RA in whom active disease persists despite treatment with multiple disease-modifying antirheumatic drugs and biologic therapies, and in some of these patients steroid treatment remains necessary despite obvious concerns about long-term side effects.…”
Section: Specific Targeting Approachesmentioning
confidence: 99%